One and only SNARC? Spatial-Numerical Associations are not fully flexible and depend on both relative and absolute number magnitude - Lilly Roth; John Caffier; Ulf-Dietrich Reips; Hans-Christoph Nuerk; Annika Tave Overlander; Krzysztof Cipora (Royal Society Open Science)
Numbers are associated with space, but it is unclear how flexible these associations are. We investigated whether the SNARC effect (Spatial-Numerical Association of Response Codes; Dehaene et al. 1993 J. Exp. Psychol. 122, 371–396. (doi:10.1037/0096-3445.122.3.371); i.e. faster responses to small/large number magnitude with the left/right hand, respectively) is fully flexible (depending only on relative magnitude within a stimulus set) or not (depending on absolute magnitude as well). Evidence for relative-magnitude dependency came from studies observing that numbers 4 and 5 were associated with the right in a 0–5 range but with the left in a 4–9 range (Dehaene et al. 1993; Fias et al. 1996 Math. Cogn. 2, 95–110 (doi:10.1080/135467996387552). Within this Registered Report, we conducted two online experiments running Bayesian analyses with optional recruitment stopping at moderate evidence (BF10 above 3 or below 1/3). Experiment 1 (n = 200) replicated relative-magnitude dependency using the original stimuli. However, Experiment 2 (n = 300) additionally demonstrated absolute-magnitude dependency, while considering recent advances in SNARC research using 1–5 excluding 3 and 4–8 excluding 6. In contrast to the frequently perpetuated notion of fully flexible Spatial-Numerical Associations, some fixed relation to absolute magnitude prevails. These findings have important consequences for understanding how Spatial-Numerical Associations might support numerical processing.